Copper-Catalyzed Ring-Opening Reactions of Alkyl Aziridines with B2pin2: Experimental and Computational Studies - Lucilla Favero; Andrea Menichetti; Cosimo Boldrini; Lucrezia Margherita Comparini; Valeria Di Bussolo; Sebastiano Di Pietro; Mauro Pineschi (Molecules, 2021)
The possibility to form new C–B bonds with aziridines using diboron derivatives continues to be a particularly challenging field in view of the direct preparation of functionalized β-aminoboronates, which are important compounds in drug discovery, being a bioisostere of β-aminoacids. We now report experimental and computational data that allows the individuation of the structural requisites and of reaction conditions necessary to open alkyl aziridines using bis(pinacolate)diboron (B2pin2) in a regioselective nucleophilic addition reaction under copper catalysis.